Thirty-Year-Old Paradigm about Unpalatable Perch Egg Strands Disclaimed by the Freshwater Top-Predator, the European Catfish (Silurus glanis) - Vejřík, Lukáš; Vejříková, Ivana; Kočvara, Luboš; Sajdlová, Zuzana; Hoang The, Son Chung; Šmejkal, Marek; Peterka, Jiří; Čech, Martin (PLoS One, 2017)
So far, perch egg strands have been considered unpalatable biological material. However, we repeatedly found egg strands of European perch (Perca fluviatilis) in the diet of European catfish (Silurus glanis) caught by longlines in Milada and Most Lakes, Czech Republic. The finding proves that perch egg strands compose a standard food source for this large freshwater predatory fish. It extends the present knowledge on catfish foraging plasticity, showing it as an even more opportunistic feeder. Utilization of perch egg strands broadens the catfish diet niche width and represents an advantage against other fish predators. Comparison of datasets from extensive gillnet and SCUBA diver sampling campaigns gave the evidence that at least in localities where food sources are limited, multilevel predation by catfish may have an important impact on the perch population.
Keywords: okounovití; Animals; Česká republika; Fresh Water; sumci; Gastrointestinal Contents; Lakes; predátorské chování; zvířata; Predatory Behavior; gastrointestinální obsah; sladká voda; Czech Republic; Perches; jezera; Catfishes